(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The aim of the present article is an analysis of national tourist organizations (NTO) concerning the promotion of states. The promotional activities of the Polish Tourist Organization (PTO) aimed at the creation of the tourist image of Poland were analyzed in a great detail. The article presents among others the amounts of financial outlays for the promotion of tourism, types and a description of the instruments of promotion used, functioning of the Polish tourist information centers abroad (PTIC) as well as the chief markets to which promotion is addressed. The article contains a research thesis, namely that an active operation of the PTO concerning promotion determines to a substantial extent the development of arrival tourism in Poland.